A Critical History of Southern Rhodesia - Thompson, Gardner (Lynne Rienner Publishers, 2024)
Gardner Thompson offers a fresh history of British rule in Southern Rhodesia, from the first colonial settlements in Mashonaland in the 1890s to the establishment of the country's sovereignty as Zimbabwe.After tracing developments in the early decades, Thompson turns to the post-World War II debate about the colony's future direction-which pitted progressive settlers against the increasingly racialist conservative core-the impact of the Unilateral Declaration of Independence in 1965, and the many damaging consequences of the choices that were made. Not least, he assesses the legacy of Rhodesian colonialism in postcolonial Zimbabwe.